2018
DOI: 10.1111/jgs.15392
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Direct‐Acting Antivirals for Hepatitis C in Older Adults

Abstract: DAA therapy is highly efficacious for the treatment of HCV in older adults, but those aged 75 and older are more likely to have clinically significant pretreatment DDIs and experience AEs, including ribavirin-induced anemia, during therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…In line with the standard numerical criterion of the United Nations, China uses a cutoff is 60+ years to refer to the elderly, which is equivalent to the legal retirement age (27). Previous studies on the efficacy of DAA therapy for older patients have mainly been based on different age groups, and the results are similarly highly efficient (17)(18)(19)32). Our study also showed that patients in three age subgroups (i.e., the age groups of 60-69, 70-79, and ≥80) had excellent SVR results.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In line with the standard numerical criterion of the United Nations, China uses a cutoff is 60+ years to refer to the elderly, which is equivalent to the legal retirement age (27). Previous studies on the efficacy of DAA therapy for older patients have mainly been based on different age groups, and the results are similarly highly efficient (17)(18)(19)32). Our study also showed that patients in three age subgroups (i.e., the age groups of 60-69, 70-79, and ≥80) had excellent SVR results.…”
Section: Discussionsupporting
confidence: 70%
“…To date, these questions remain unanswered, as the data are limited, which is mainly due to the fact that older patients are usually excluded or underrepresented in clinical trials (3). Further, the majority of real-world studies that have examined the treatment outcomes and safety of DAA therapy among older HCV patients have been conducted in Western countries (14)(15)(16)(17)(18); thus, the data for Asian countries are very limited (19,20). Additionally, these studies (I) focused on only one DAA regimen (14,21), (II) considered only one HCV genotype (15,20,22), or (III) lacked power due to their limited sample sizes (16,19).…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the course of HCV infection in this older population. Early reports suggest similar efficacy of direct-acting antiviral (DAA) therapy in older patients but increased risk of adverse events in those over the age of 75 [12]. Given the rarity of documented risk factors in this cohort, it is unclear how and when the majority of these patients were initially infected.…”
Section: Discussionmentioning
confidence: 95%
“…Elderly people often experience multi-morbidities (either due to aging or to HCV itself), take comedications, and most likely also have a long history of hepatic disease, even for the risk factors associated with the infection in Italy [2]. All these characteristics (advanced age, comorbidities, and high burden of comedications) could potentially affect tolerability of HCV treatment and adherence in this subgroup [7]. Moreover, some possible side effects and biomarker alterations, as well as increased risk of liver cancer, have been reported by several authors, especially in elderly people [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%